Conjugation of a Cationic Cell-Penetrating Peptide with a Novel Kunitzin-like Trypsin Inhibitor: New Insights for Enhancement of Peptide Bioactivities - Junting Yao; Weining Yin; Yuqing Chen; Xiaoling Chen; Yangyang Jiang; Tao Wang; Chengbang Ma; Mei Zhou; Tianbao Chen; Chris Shaw; Lei Wang (MDPI AG, 2022)
Cationic cell-penetrating peptides (CPPs), such as transactivator of transcription (TAT) peptide, have been proposed as effective drug carriers to improve intracellular delivery of biological macromolecules. Amphibian skin-derived Kunitz-type trypsin inhibitors (KTIs), short counterparts of KTIs from plant sources, were found to possess potent serine protease inhibitory activity. However, poor transmembrane permeability of these molecules has largely hindered the study of the full spectrum of their biological actions. As a result, this study aimed to extend the biological activities of amphibian KTIs by their conjugation to cationic CPPs. Herein, a novel peptide (kunitzin-OV2) and its phenylalanine-substituted analogue F9-kunitzin-OV2 (F9-KOV2) were evaluated for inhibition of trypsin/chymotrypsin and showed weak antibacterial activity against Escherichia coli (E. coli). As expected, the conjugation to TAT peptide did not increase membrane lysis compared with the original kunitzin-OV2, but effectively assisted this complex to enter cells. TAT-kunitzin-OV2 (TAT-KOV2) exhibited a 32-fold increase in antibacterial activity and an enhanced bactericidal rate against E. coli. In addition, the conjugation enabled the parent peptides to exhibit antiproliferative activity against cancer cells. Interestingly, TAT-F9-kunitzin-OV2 (TAT-F9-KOV2) showed stronger antiproliferative activity against human breast cancer (MCF-7) and human glioblastoma (U251MG) cell lines, which TAT-KOV2 did not possess. Moreover, TAT-F9-KOV2 showed a 20-25-fold increase in antiproliferative capacity against human lung cancer (H157, H460) cell lines compared with TAT-KOV2. Therefore, the conjugation of CPPs effectively solves the problem of cell penetration that short KTIs lack and provides evidence for new potential applications for their subsequent development as new antibacterial and anticancer agents.